Synthesis of 1,5-Anhydro-d-glycero-d-gluco-heptitol Derivatives as Potential Inhibitors of Bacterial Heptose Biosynthetic Pathways - Blaukopf, Markus; Atamanyuk, Dmytro; Xavier, Nuno M.; Gerusz, Vincent; Kosma, Paul (Synthesis, 2017)
A series of 1,5-anhydro-d-glycero-d-gluco-heptitol derivatives have been prepared from 3-O-benzyl-1,2-O-isopropylidene-d-glycero-d-gluco-heptofuranose via conversion into anomeric bromide and thiophenyl derivatives, followed by glycal formation and reductive desulfurization, respectively. Global deprotection of the protected intermediates afforded the 1,5-anhydro derivatives of the d-glycero-d-gluco- and 1,2-dideoxy-d-altro- configuration as well as the 1,5-anhydro-2-deoxy-d-altro-hept-1-enitol. In addition, the 7-O-phosphorylated d-glycero-d-gluco-heptose and its 1,5-anhydro analogue were prepared in good yields utilizing phosphoramidite chemistry. A novel heptitol analogue based on a 1-deoxynojirimycin scaffold was also elaborated via a Wittig-type chain elongation followed by dihydroxylation, separation of the resulting epimers, and global deprotection. The target compounds, however, were not active as inhibitors of the bacterial sedoheptulose-7-phosphate isomerase GmhA.
Keywords: heptose; carbohydrates; inhibitor; anhydro-sugar; C6 chain elongation; phosphorylation